Effect of response method in participants with sensorineural hearing loss - Mishra, Rajkishor; Sahu, Preeti; Mahallik, Debadatta (International Journal of Research in Medical Sciences, 2017)
Background:Aim of the study was to compare the speed of response, false-alarm rate, and subject preference of different response methods i.e. raising a hand, using response switch, and oral response mode for measuring pure-tone thresholds. Methods:Forty five participants (female-21 and 24 male) were included in the study with sensorineural hearing loss of various degree. Response method order was randomly assigned to 3 different sessions. Air-conduction thresholds were measured thrice for each participant in octave intervals between 250 Hz and 8000 Hz. The 2nd and 3rd session were performed for different response method on a different day but within 2 weeks of the 1st session. Results:Difference in the time was noted when compared with the extent of time required to complete the test for each response method. On an average, using the pushbutton method took 3.02 to 3.42 minutes less than using hand-raise or verbal response methods. There was also a significant participant preference for using the response button. No significant difference between response method for threshold level and number of false positives (P = 0.15) was found. Conclusion:This study supports the use of the response button when measuring auditory thresholds for sensorineural hearing loss.